STRATEGI PEMASARAN JASA PENDIDIKAN DALAM MENINGKATKAN CITRA DI PONDOK PESANTREN MADINATUL ULUM MERANGIN - Lili Apriani; Minna El Widdah; Muslih Muslih (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Marketing of educational services needs to be carried out as a form of accountability to provide information regarding the condition of Islamic boarding schools to the public. This study aims to determine the marketing mix strategy of educational services carried out by Pondok Pesantren Madinatul Ulum Merangin in improving its image. This study uses a descriptive qualitative approach. Data collection techniques with interviews, observation and document study. Data analysis techniques with data reduction, data presentation and drawing conclusions. The results showed that overall the Madinatul Ulum Merangin Islamic Boarding School had implemented an educational service marketing strategy that was quite good in improving its image. By providing a product offer that suits the needs of the community, and a strategic location for Islamic boarding schools to carry out educational activities and carry out promotions through student guardians, print media, social media and output. Madinatul Ulum Merangin Islamic Boarding School provides coaching for teachers, and the learning process is quite good. However, in the aspect of physical evidence, the facilities and infrastructure provided are inadequate and it is better to improve the facilities provided by Islamic boarding schools so that they are able to support the implementation of a quality education process.